Cardiac functional status of patients with Chronic Kidney Disease: A cross sectional study (Bangladesh Critical Care Journal, 2022)
Background: In the recent years, the prevalence of chronic kidney disease (CKD) has increased in the community. CKD has been associated with several cardiac diseases. The aim of the study was to assess the cardiac status of the CKD patients.Methods: This cross-sectional study was done in Rangpur Medical College Hospital, Rangpur from June 2013 to November 2013. A total of 50 CKD patients were selected by convenient type of sampling. An informed written consent was taken before enrolling the patients into the study. All the data were recorded in a pre-structured questionnaire. Analysis of the data was done by SPSS V.22. A P value of